2020
DOI: 10.1007/s40204-020-00131-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in mechanical properties and biodegradability of PLA using poly(ethylene glycol) and triacetin for antibacterial wound dressing applications

Abstract: Wound is among the most common injuries. A suitable wound dressing has a significant effect on the healing process. In this study, a porous wound dressing was prepared using poly (lactic acid) (PLA) and two plasticizers, polyethylene glycol (PEG) and triacetin (TA), through solvent casting method. For antibacterial activities, metronidazole was incorporated in the structure. The morphology was investigated by scanning electron microscopy (SEM). In addition, the effect of plasticizers ratio on porosity growth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 36 publications
(40 reference statements)
4
24
0
Order By: Relevance
“…Similar results were obtained by Darabian et al; in their study, they examined two different plasticisers. As to the absorption, the results clearly showed that a similar phenomenon has been observed in the samples containing polylactic acid (PLA) and TAC, in particular that the water absorbency increases with an increasing TAC [ 7 ].…”
Section: Introductionmentioning
confidence: 69%
“…Similar results were obtained by Darabian et al; in their study, they examined two different plasticisers. As to the absorption, the results clearly showed that a similar phenomenon has been observed in the samples containing polylactic acid (PLA) and TAC, in particular that the water absorbency increases with an increasing TAC [ 7 ].…”
Section: Introductionmentioning
confidence: 69%
“…It was observed that modification of alginate with TA and TBC increased the degradation rate of the scaffolds ( P < .05). Darabian et al expressed that TA decreased PLA scaffold degradation 28 . Kurowiak et al demonstrated that the mass of alginate hydrogels cross‐linked with Ca‐Ba was about 18% 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al also used triacetin for starch ester films, and they observed that triacetin decreased the thermal stability of starch film 36 . Darabian et al reported that mixing TA decreased melting enthalpy of poly lactic acid scaffold 28 …”
Section: Resultsmentioning
confidence: 99%
“…However, many pores were detected on the PLLA film matrices when the PEG was blended. These pore structures occurred from the infiltration of blended PEG and solvent into bulk PLLA during solvent evaporation [35,36]. Coalescence of these pores was detected for the 80/20 PLLA/PEG blend film [Fig.…”
Section: Phase Morphologymentioning
confidence: 99%